ANALISIS PENGARUH SEDIMENTASI TERHADAP PENGURANGAN NILAI FUNGSI DARI KAPASITAS SALURAN DRAINASE DI JALAN LINTAS TANO-SUMBAWA: ANALISIS PENGARUH SEDIMENTASI TERHADAP PENGURANGAN NILAI FUNGSI DARI KAPASITAS SALURAN DRAINASE DI JALAN LINTAS TANO-SUMBAWA - Eti Kurniati; Aruna Wijaya; Totok Hari Dewanto; Tri Susilawati (Hexagon Jurnal Teknik dan Sains, 2022)
The Tano – Sumbawa cross road is one of the national highways that connects two regencies, namely West Sumbawa Regency and Sumbawa Regency. Meanwhile, the research location is in Luk Village, Rhee District, Sumbawa Regency, precisely at Km 14+100 to 14+600. As we know that, Drainage is one of the water building facilities that functions to drain, dry a land so that the land can be used optimally. Good drainage is expected to overcome the damage to the highway caused by water. There are so many problems that we often encounter in drainage channels, one of which is the deposition of sedimentation which can result in a reduction in the value of the drainage channel function so that the drainage channel cannot work optimally. So we need a study with the aim of knowing the type of sedimentation in the drainage channel of the Tano - Sumbawa highway and to find out what percentage of the sedimentation rate is in the drainage channel so that with the aim of knowing what steps should be taken in dealing with damage to the drainage channel. caused by sedimentation in drainage channels. To find out the type of sedimentation, the Grain Size Distribution Analysis was used, while to find out the percentage of sedimentation rate in the Drainage channel, the Sediment Percentage Analysis method was used. From the results of the study, the diameter of the average grain size of the sedimentation aggregate was 0.71 mm and it was said to be medium sand. Meanwhile, the percentage of sedimentation in the canal was found to be 84.90% and it was said to be dysfunctional, as for the steps that should be taken, namely to conduct a design study of the drainage channel.